2023
DOI: 10.1111/pbi.14215
|View full text |Cite
|
Sign up to set email alerts
|

Upland rice genomic signatures of adaptation to drought resistance and navigation to molecular design breeding

Yulong Wang,
Conghui Jiang,
Xingtan Zhang
et al.

Abstract: SummaryUpland rice is a distinctive drought‐aerobic ecotype of cultivated rice highly resistant to drought stress. However, the genetic and genomic basis for the drought‐aerobic adaptation of upland rice remains largely unclear due to the lack of genomic resources. In this study, we identified 25 typical upland rice accessions and assembled a high‐quality genome of one of the typical upland rice varieties, IRAT109, comprising 384 Mb with a contig N50 of 19.6 Mb. Phylogenetic analysis revealed upland and lowlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Wei et al, studied eight genome-wide association-based research cohorts (QTNs), mapped rice quantitative trait nucleotides (QTNs) and inferred QTN effects, which illustrated that molecular markers can be used to resolve the genetic drag caused by uneven genome distribution when QTGs are mapped [76]. Wang et al, also conducted a comprehensive study integrating the genome, transcriptome, and population analysis of rice, identified key candidate genes for drought adaptation in upland rice (UR), and constructed a genomic navigation map for drought-resistant breeding in rice, revealing the crucial role of accumulated highland-specific variations in enhancing drought tolerance [77]. The application of molecular navigation breeding significantly enhances the efficiency of rice breeding, optimizes the cultivation of new varieties, and provides scientifically effective guidance for rice-breeding design.…”
Section: Genome-wide Molecular Navigation Breedingmentioning
confidence: 99%
“…Wei et al, studied eight genome-wide association-based research cohorts (QTNs), mapped rice quantitative trait nucleotides (QTNs) and inferred QTN effects, which illustrated that molecular markers can be used to resolve the genetic drag caused by uneven genome distribution when QTGs are mapped [76]. Wang et al, also conducted a comprehensive study integrating the genome, transcriptome, and population analysis of rice, identified key candidate genes for drought adaptation in upland rice (UR), and constructed a genomic navigation map for drought-resistant breeding in rice, revealing the crucial role of accumulated highland-specific variations in enhancing drought tolerance [77]. The application of molecular navigation breeding significantly enhances the efficiency of rice breeding, optimizes the cultivation of new varieties, and provides scientifically effective guidance for rice-breeding design.…”
Section: Genome-wide Molecular Navigation Breedingmentioning
confidence: 99%